2001
DOI: 10.12681/mms.263
|View full text |Cite
|
Sign up to set email alerts
|

Stock assessments of the Black Sea anchovy during the period 1979-1993

Abstract: The stock assessments of the Black Sea anchovy during the period 1979-1993 were made by Age- and Length-structured VPA. According to the obtained results, the initial anchovy exploited biomass varied from 1421.3 (1979) to 243.3 thousand tons (1990). In 1979 the mean exploited biomass was 1036.5 thousand tons. Both assessments are very close because the mean biomass at F=0.5 has to be 73.71% from the initial one.The comparatively low level of fishing activity from 1968-1977 (mean value of F was 0.2407) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In the study conducted by Solak (2015), the K value of anchovy was found to be 2.06 for females and 1.03 for males, while it was determined to be 0.43 for both sexes in the study conducted by Sağlam & Sağlam (2013). In their study in the Strait of Sicily, Basilone et al (2006) calculated the growth constant (K) of anchovy as 0.3; in the study conducted by Prodanov & Stoyanova (2001) in the Black Sea, it was calculated as 0.308. On the Algerian coasts (SW Mediterranean), it was calculated as 0.87 (Bacha et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In the study conducted by Solak (2015), the K value of anchovy was found to be 2.06 for females and 1.03 for males, while it was determined to be 0.43 for both sexes in the study conducted by Sağlam & Sağlam (2013). In their study in the Strait of Sicily, Basilone et al (2006) calculated the growth constant (K) of anchovy as 0.3; in the study conducted by Prodanov & Stoyanova (2001) in the Black Sea, it was calculated as 0.308. On the Algerian coasts (SW Mediterranean), it was calculated as 0.87 (Bacha et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Asymptotic lengths ( L ∞ ) were estimated for anchovy in various studies conducted throughout different fishing seasons in the Black Sea. In their research in the eastern Black Sea, Prodanov & Stoyanova (2001) calculated the L ∞ value as 17.09 cm. On the Bulgarian coast, Yankowa (2014) found the L ∞ value as 14.60.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation